Pencegahan Penyalahgunaan Narkoba Melalui Pendidikan Karakter Dalihan Na Tolu Pada Siswa SMA Negeri 4 Kota Padangsidimpuan - Indra Purba Harahap; Rica Gusmarani; Syukron Firdaus Siregar (Departement of Mathematics Education, 2024)
The government issued Law Number 22 of 1997 replaced by Law Number 35 of 2009 concerning Drugs to prevent the adverse effects of drugs. However, the Drug Law has not been able to prevent the increase in drug abuse, especially at the high school level. Dalihan na tolu character education is considered to have a significant effect on preventing drug abuse. The purpose of the study was to find out how the influence of dalihan na tolu character education on drug abuse prevention. The type of research conducted is quantitative with a descriptive approach. The research instrument uses questionnaires. The results of the study stated that Dalihan Na Tolu Character Education had a positive and significant effect on the Prevention of Drug Abuse in students of SMA Negeri 4 Padangsidimpua Town. If dalihan an tolu character education is improved, drug abuse prevention will increase in SMA Negeri 4 Padangsidimpuan Town.